Wage Bargaining and Partial Ownership - Bárcena Ruiz, Juan Carlos; Campo, María Luz (Estudios de Economía, 2016)
This paper analyzes wage negotiation between firms and unions when crossparticipation exists at ownership level. We consider two shareholders and two firms: one firm is jointly owned by the two shareholders and the other is owned by a single shareholder. Labor is unionized and the firms produce substitute products. We show that partial ownership increases the bargaining strength of the firm owned by a single shareholder; although this firm pays lower wages produces less output than the other firm. Compared with the case in which each firm is owned by a single shareholder, partial ownership reduces the wage paid by firms, the output of industry and therefore employment. Whether firms obtain greater or lower profit depends on the degree to which goods are substitutes. In fact, we obtain the surprising result that when the degree to which goods are substitutes is low enough, the firm that is owned by a single shareholder makes more profit than the other firm.